Understanding the sustainable development goals concept Malaysia report and trend - Nik Athirah, Nik Mahdi; Fernando, Yudi; Abdalla, Yousif Abdelbagi (UMP Publisher, 2023)
The desire to go even further in eradicating poverty in all aspects, dealing with climate change and eliminating inequalities has established the 2030 Agenda of Sustainable Development Goals (SDGs) in September 2915. The world leader adopted it at the historic UN summit. Malaysia has long sought to achieve the 2030 Agenda. The satisfaction degree of accomplishment of sustainable development the still low. Thus, this paper aims to shed light on the trend of sustainable development goals in Malaysia, which provides the community with information on a council's sustainable development goals. This has concluded Malaysia's three main SDG patterns, including reducing inequalities, climate action, and zero hunger. This study has concluded that the SDGs are crucial for achieving a better quality of life and sustainability. The SDGs' achievement does not solely depend on the government and its responsibility to all stakeholders. It is suggested that the better improvement of SDGs and better achievement, this study argue that government, industry, community and civil society organisations to work together to achieve shared and sustainable prosperity.